Implementasi Shalat Tahajud dalam Pembentukan Kedisiplinan Santri di Pondok Pesantren Putri Roudhotul Qur’an Cukir Jombang - Muhammad Arif Ridwan (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2017)
Tahajud prayer is virtue and value of worship provides many benefits, even though the ruling muakkad sunnah. This article discusses the implementation of tahajud prayer in the Qur'an Roudhotul Daughter boarding schools Cukir specialized in Jombang, this pesantren rather mandatory, as well as the constraints encountered. This article is a qualitative field research results (grounded) and descriptive qualitative approach-phenomenology. Source of research data is the result of interviews with the sitters, ustadz and caretaker of the boarding school. The study also used the document as a data source. The technique of data collection is done with the interview, observation and documentation. This article concludes that implementation of the prayer in the formation of tahajud discipline students in boarding schools is running well because the Congregation is executed, so the passion in students appreciate the time, students will be more enterprising and used to living clean and shape the students for being true and abiding by the rules that have been set. This form of discipline students in boarding schools include time discipline, discipline, discipline and cleanliness of dress a disciplined behaviour. Obstacles faced this boarding schools in implementing the prayer in congregation whom tahajud santri lazy wake up or with a variety of other reasons that made so as not to participate in congregation tahajud prayer. But those constraints thus become its own zeal for the caretakers and stewards for being able to change bad habits into good habits.